Air power in UN operations wings for peace - Dorn, A. Walter (Military strategy and operational art, 2014)
Air power for warfighting is a story that's been told many times. Air power for peacekeeping and UN enforcement is a story that desperately needs to be told. In rich detail this volume describes: aircraft transporting vital supplies to UN peacekeepers and massive amounts of humanitarian aid to war-affected populations; aircraft serving as the ""eyes in sky"" to keep watch for the world organization; and combat aircraft enforcing the peace. Rich poignant case studies illuminate the past and present use of UN air power, pointing the way for the future.